2011
DOI: 10.1364/oe.19.013164
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous gold plasmonic structures for sensing applications

Abstract: The fabrication, characterization and functionalization of periodically patterned nanoporous gold layers is presented. The material shows plasmonic properties in the near infrared range, with excitation and propagation of surface plasmon polaritons. Functionalization shows a marked enhancement in the optical response in comparison with evaporated gold gratings, due to a great increase of the active surface. Due to its superior response, nanoporous gold patterns appear promising for the realization of compact p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 17 publications
3
44
0
Order By: Relevance
“…Due to the known performance advantages, considerable efforts have been made to explore potential applications of nanoporous materials in various fields, such as catalysis, sensors, actuators, fuel cells, energy storage, bioelectrochemistry, plasmonic metamaterials, etc. [4,5,6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…Due to the known performance advantages, considerable efforts have been made to explore potential applications of nanoporous materials in various fields, such as catalysis, sensors, actuators, fuel cells, energy storage, bioelectrochemistry, plasmonic metamaterials, etc. [4,5,6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…For this reasons, the cornet appears brown in colour [18][19][20][21][22]. This very interesting behaviour of nanoporous gold and gold nanoparticles has been studied also for many different applications, such as monitoring body fluids, new electronic devices and decorative effects [23][24][25][26][27][28][29][30][31].…”
Section: Cornet Stagementioning
confidence: 99%
“…In most cases, both SPP and LSP resonances are present and contribute to the optical characteristics of the nanostructure. Plasmonic resonances are sensitive to the changes in refractive indices due to molecular adsorption on the metallic surface [2,3]. With regard to this phenomenon we demonstrated that a nanoporous gold (NPG) substrate can improve the sensitivity of a surface plasmon resonance (SPR) based biosensor, taking advantage of the high surface to volume ratio of the material.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to this phenomenon we demonstrated that a nanoporous gold (NPG) substrate can improve the sensitivity of a surface plasmon resonance (SPR) based biosensor, taking advantage of the high surface to volume ratio of the material. The experimental verification was performed on a digital grating by measuring the SPR shift in reflectance and transmittance in the visible range [2][3][4][5]. The research efforts are still focused on the quest for novel plasmonic materials.…”
Section: Introductionmentioning
confidence: 99%